Metallomics and mass spectrometry for drug development: ICP-MS and MALDI TOF MS for assessment of protein-drug interactions - Masnikosa, Romana; Rilak-Simović, Ana; Veličković, Suzana (Biologia Serbica, 2020)
Ever since the discovery of the anticancer drug cisplatin, the field of inorganic medicinal chemistry has been expanding. A plethora of metal-based compounds (Pt, Ru, Au, Pd, Cu) containing organic or inorganic ligands (NH3, Cl, DMSO, η6-arene, imidazole, indazole, terpyridine, phosphoadamantane) has been developed with the aim to find new and improved anticancer therapeutics, which would have less side-effects, and to overcome tumour resistance. The medicinal inorganic chemistry community must determine: how these compounds enter living cells, how they distribute inside cells, what are their intracellular targets, how they behave in circulation (free vs protein-bound fraction), what are their target tissues, and what biomolecules are responsible for their transport to biological targets. All of these questions have been recently addressed with the aid of different mass spectrometry (MS) techniques. Inductively coupled plasma MS is a highly sensitive method for determining the metal content in biological samples. Matrix-assisted laser desorption/ionisation and electrospray MS are used to characterise adducts between metallodrugs and proteins. MS methods provide information on binding kinetics, binding parameters, the nature of the adducts and target sequences in proteins. This review deals with the most interesting results obtained by the most influential mass spectrometrists working in the field of inorganic biochemistry.